BUDAYA LITERASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MELALUI KEGIATAN WAKPIJAR - Pratiwi, Anggi Dwi; Kusuma, Apriadi Marki; Feranda, Erika; Al-Islami, Ilma; Ericson, Kresensius (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
The ability to think critically and creatively is an important aspect for developing individual potential in the era of globalization. To improve these skills, the Literacy Culture Activity Program is implemented with an innovative and interesting approach called WAK PIJAR (Pontianak Active Learning Time). This program aims to invite children to actively participate in reading and writing activities, focusing on improving critical thinking and creative thinking. Through WAK PIJAR, children are invited to participate in reading, writing, and discussion activities that stimulate critical thinking, and encourage imagination and creativity. WAK PIJAR activities are delivered in a planned and structured manner by involving students in group discussions, text analysis, and creative writing. In addition, there are demonstration sessions and games are also held which stimulate innovation. The result of the WAK PIJAR program is that the children who take part in this activity experience an increase in their ability to think critically and creatively.